Sanihair / Nuraisyah Nawawi - Nawawi, Nuraisyah (2020)
Nowadays, many people start worrying about their health for almost all parts of their body including their hair. Sanihair will provide the solution to prevent the presence of the bacteria, germs, and virus on people’s hair. We can avoid the contamination of these bad bacteria, germs, and viruses to the public community especially for those who are staying in the big cities since this place has many areas of crowd people. Area with crowded people is a good portal for these bacteria, germs, and viruses to transmit from one person to another. Therefore, Sanihair is very important for those who stay in the big city. Despites, the Sanihair also contains zero amounts of ingredients that can make your hair dry when applied which is an alcohol. This Sanihair is only made from organic ingredients such as coconut oil, lavender essential oil, witch hazel essential oil, and lemon essential oil. These ingredients function as an antimicrobial, anti-inflammatory, anti-fungal, and antidepressant which are good for self-therapy. The structure of these Sanihair is oily- based but very easy to absorb on your hair even on skin too. Other than that, Sanihair products also come along with a skin analyzer. The skin analyzer functions to measure your skin's moisture which is the level of water and oil on your head skins. Even this Sanihair has two ways to use, the size is still very compact and pocket friendly which means the user can easily put these Sanihair on pocket and handbags. We will introduce this new technology to the public, in order to reduce transmission of bad bacteria, germs, and viruses to our communities nowadays. Therefore, we can always stay in a health and safe community. This Sanihair has functions and advantages not found in today's common sanitizer thus, providing a competitive advantage over more established competitors.